Natural Disasters Versus Anthropogenic Activities in Nepal Himalayas: Case Study from Ghatte Khola , Myagdi - Gurung, Narayan (Technical Journal, 2019)
In the Himalayas, geo-hazards are natural events occurring more or less frequently and of a greater or lesser magnitude. But when natural hazards affect people and property, then it becomes disasters. It’s believed that natural disasters as such do not exist. Everything is just natural hazard and anything can turn into disasters due to anthropogenic activities. Thus, natural phenomenons are hazards while disasters are anthropogenic. In this regard, a case study was being conducted in the Ghatte Khola (Dana) of Myagdi District in Western Central Nepal, where in a context of growing population and haphazard construction of infrastructures, natural dynamics have turned into disasters. The Ghatte Khola is an intermittent, right bank tributary of the Kali Gandaki, which behaves occasionally as a debris flow, in relation with slope instabilities that affect its upstream catchment. The debris flows are usually triggered during heavy cloudbursts, and can cause damages and losses downstream, along the wide alluvial fan built at the tributary junction and upon which Dana village (Myagdi District) is settled. Inhabitants are aware of this ephemeral, yet threatening behaviour of the stream that may also affect the Kali Gandaki valley upstream from the confluence (Lat. 28°32'22" N and Long. 83°39'03" E). The Ghatte Khola is often affected by debris flows bringing sediment fluxes that are eroding its banks every year. A motor bridge was being built over Ghatte Khola near the confluence with Kali Gandaki and further, a large electric power station is being built on the right bank of Ghatte Khola. Sadly, the bridge was washed away by the flash flood in Ghattekhola on 25th May 2019. This study was focused on vulnerability of these man made infrastructures and their future on Ghatte Khola debris flow dynamics, with hazard that might occasionally transform into disaster.